Safety assessment of deutetrabenazine: real-world adverse event analysis from the FAERS database - Shu, Yanping; Wang, Yuanhe; Liu, Jiaoying; Hu, Lingyan; Tong, Sichao; Wu, Gang; Zhu, Xianlin (Frontiers in Pharmacology, 2024)
BackgroundDeutetrabenazine is a widely used drug for the treatment of tardive dyskinesia (TD), and post-marketing testing is important. There is a lack of real-world, large-sample safety studies of deutetrabenazine. In this study, a pharmacovigilance analysis of deutetrabenazine was performed based on the FDA Adverse Event Reporting System (FAERS) database to evaluate its relevant safety signals for clinical reference.MethodsAdverse events (AEs) of FAERS with deutetrabenazine as the primary suspect drug were collected from the first quarter (Q1) of 2017 to Q1 of 2024. Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Empirical Bayesian Geometric Mean (EBGM) were used to mine AEs risk signals of deutetrabenazine. AEs were standardized and classified using the System Organ Class (SOC) and Preferred Terms (PTs) from Medical Dictionary for Regulatory Activities (MedDRA) version 23.0.ResultsA total of 3,583 AEs with deutetrabenazine as the primary suspect drug were collected in this study. We found that these AEs involved 23 SOCs, and the positive signals were mainly concentrated in systemic disease and various reactions at the site of administration (n = 1816, ROR = 1.23, PRR = 1.18, IC = 0.24, EBGM = 1.18), neurological disorders (n = 1736, ROR = 3.02, PRR = 2.60, IC = 1.38, EBGM = 2.60) and psychiatric disorders (n = 1,659, ROR = 4.15, PRR = 3.52, IC = 1.82, EBGM = 3.52). We eventually identified 100 valid PTs that met the criteria of the four algorithms. Drug ineffective, dyskinesia, depression, somnolence, suicidal ideation were considered to be the common PTs of deutetrabenazine. Tongue thrust (n = 4, ROR 253.47, PRR 253.35, IC 7.88, EBGM 235.95), grunting (n = 5, ROR 78.49, PRR 78.45, IC 6.26, EBGM 76.71) and drooling (n = 17, ROR 13.21, PRR 13.19, IC 3.72, EBGM 13.14) were not mentioned in the specification, but the high signal intensity suggested that they may be the potential adverse reactions.ConclusionThe efficacy of deutetrabenazine may be accompanied by some potential adverse effects in several systems. Adverse events in psychiatric, neurologic, gastrointestinal and respiratory need to be monitored in clinical practice.